The Methodology of Sociological Research in the Composit Society - A. Y. Trufanov (Vestnik MGIMO-Universiteta)
The article highlights the problems encountered in sociological research, the customer is State authorities of subjects of the Russian Federation. Also the article discusses the methods of picking the participants of placing the order as an open electronic auction, open tender, quoted bid. The article contents comparative analysis of given methods, considers their benefits and limitations, touches on the practical questions associated with the funtioning one or the other method.